The effectiveness of "RS Centing” intervention to improve knowledge and behavior among adolescents to prevent stunting - Has, Dwi Faqihatus Syarifah; Ariestiningsih, Eka Srirahayu; Mufidah, Rina Zahrotul; Sholihah, Mar'atus (Pediomaternal Nursing Journal, 2024)
Introduction: Based on data from the 2021 Indonesian Nutritional Status Study (SSGI), the prevalence of stunting in Gresik Regency is 23%, close to the prevalence rate of stunting in East Java of 23.5%. Despite the decline, stunting is still a challenge for the government. The Gresik Regency government is focusing on ten sub-districts as priority focus locations for reducing stunting, one of which is the Kebomas Sub-District. Therefore, the researchers analyzed the implementation of Remaja Sehat Cegah Stunting/Healthy Youth Posyandu Prevent Stunting (RS Centing) program, which focuses on educating youth about stunting. Methods: Pre-experimental research, with a population of 75 teenagers, was selected based on inclusion: (1) age criteria (17-21 years old), (2) respondents who actively participate in youth activities, and (3) live in areas focused on stunting. The sampling technique used simple random sampling, which obtained 64 respondents. The dependent variable is adolescents' level of knowledge and attitudes toward stunting”data analysis using simple linear regression analysis test. The research (1) gives a pre-test about knowledge and behavior for preventing stunting, (2) the "RS Centing” program provides assistance and outreach to young people in stunting focus locations. Then, (3) after assisting for three months, the team gave a post-test knowledge and behavior about stunting. The instruments used to conduct the research were questionnaires, pre and post-respondent knowledge, and behavior towards stunting, which would be given to respondents by Google link.Results: There was an influence of the RS Centing program on increasing knowledge (P-value <0.01) and attitudes (P-value <0.01) of adolescents in preventing stunting in Kebomas District, Gresik. Conclusion: The knowledge factor has the greatest influence (P-value 0.041, and relative value 0.000-0.376). Through this research, the Gresik Regency Government can optimize the RS Centing Program to reduce stunting in the Gresik Regency and achieve a stunting prevalence target of 10% in 2024. Keywords: attitudes of adolescents; knowledge; stunting